Effects of Regular Physical Activity on Metabolic, Cardiovascular and Cancer Outcomes: A Review of Current Evidence - Załęski, Daniel; Krankiewicz , Michał; Berdzińska , Martyna; Jusiak, Justyna; Halik, Paulina (Quality in Sport, 2026)
Introduction. Physical activity is a key determinant of population health and plays a central role in preventing and managing chronic diseases, including obesity, cardiovascular diseases, type 2 diabetes and certain cancers. Despite strong evidence, global inactivity remains high, contributing to rising metabolic and cardiovascular burdens. Materials and Methods. This review synthesizes evidence from systematic reviews, meta-analyses, randomized controlled trials, and international guidelines , focusing on physical activity, exercise physiology, obesity, cardiovascular diseases, diabetes, and cancer prevention. Results. Regular physical activity improves health across major chronic diseases. In obesity, 150–300 minutes of aerobic activity per week plus resistance training reduces body fat, especially visceral adiposity. For cardiovascular diseases, recommended activity levels lower incidence by 14–22% and mortality by 28–40%. In type 2 diabetes, structured exercise ≥8 weeks reduces HbA1c by 0.4–1.0% and improves insulin sensitivity independently of weight loss. Moderate-to-vigorous activity decreases the risk of colorectal, breast, and endometrial cancers, with probable benefits for kidney, bladder, and gastric cancers. Discussion. Benefits of physical activity are mediated via cardiovascular, metabolic, anti-inflammatory, and immune pathways and occur across all ages, independent of weight loss. Barriers such as lack of time, low motivation, and limited access to safe environments highlight the need for systemic interventions, including public health policies, environmental planning, and community programs Conclusions. Regular physical activity is essential for preventing and managing chronic diseases. Even moderate exercise delivers significant cardiovascular, metabolic, and oncologic benefits, while higher volumes and mixed modalities enhance protection.